Construct Validity of Career Adaptation in Counseling: Adaptability Ability Scale Using Structural Equational Modeling (SEM) - Hidayat, Dede Rahmat; Handika, Mardy; Herdi, Herdi; Fitriyana, Nur (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
This study aims to adapt the Career Adapt-Abilities Scale (CAAS) instrument developed by Savickas & Porfeli (2012). In this study, the main objective is the process of adapting a scale or instrument called the Career Adapt-Ability Scale (CAAS) which will be carried out in DKI Jakarta at the high school, vocational, and Madrasah Aliyah levels. The flow in carrying out the adaptation in this research is to translate from the original language into Indonesian through predetermined stages. Analysis of the data used in this study is to use the method of Structural Equational Modeling (SEM) with Amos 24.0 for windows. The sample in this study is 1.345 where the validity and reliability test results are in the high category and the goodness of fit test is high. Based on the results of this study, it can be concluded that the CAAS Scale can be used as an expression tool in career construction at the high school, vocational, and madrasah aliyah levels in DKI JAKARTA.